The performance of Gauss Markov’s mobility model in emulated software defined wireless mesh network - Tsehay Admassu Assegie; Pramod Sekharan Nair (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Wireless mesh networks (WMNs) are a new trend in wireless communication promising greater flexibility, reliability, and performance over traditional wireless local area networks (WLANs).Test bed analysis and emulation plays an important role in evaluation of wireless networks and node mobility is the prominent feature of next generation wireless network. In this paper we will focus on the models of wireless station mobility and discuss their importance within the software defined wireless mesh network performance evaluation. The existing mobility models for the next generation software defined wireless network will be explored. Finlay, we will present the mobility models in the mininet-Wi-Fi test bed, and evaluate the performance of the models